The Influence of Work Discipline as a Mediator of the Relationship between Work Motivation and Work Culture on the Sustainability Performance of Bid Personnel Public Relations of Polda Metro Jaya - Suliscianty, Cindy; Aulia, Irfan Noviandy (IJOSMAS, 2025)
The Public Relations Division of the Metro Jaya Police is facing a decline in organizational performance with a decrease in counter opinion activities by 63.5% in 2024, indicating problems in human resource management related to discipline, motivation, and work culture of personnel. This study aims to analyze the influence of work motivation and work culture on sustainable performance with work discipline as a mediating variable. The research method used a quantitative approach with causal design through the analysis of Partial Least Square-Structural Equation Modeling (PLS-SEM) on 60 personnel respondents using a five-level Likert scale questionnaire. The results showed that work motivation and work culture had a significant positive effect on work discipline with t-statistics of 3.913 and 3.177, the three predictor variables had a significant effect on sustainable performance, and work discipline was proven to mediate the relationship between work motivation (t-statistic: 2.923) and work culture (t-statistic: 2.175) on sustainable performance with a Goodness of Fit of 0.471. In conclusion, increased motivation and work culture will be more effective in improving sustainable performance when mediated by strong work discipline. It is suggested that the implementation of integrated programs includes a transparent reward system and strengthening a culture of professionalism.